Effectiveness of Health Literacy Enhancement Integrated with Telehealth in People Newly Diagnosed with Hypertension in Suburban Thailand: A Quasi-Experimental Study. - Addjanagitti, Pimlapas; Partiprajak, Suphamas; Neelapaichit, Nareemarn (Pacific Rim International Journal of Nursing Research)
People newly diagnosed with hypertension often have insufficient health literacy and suboptimal self-care behaviors, particularly in diet, physical activity, and medication adherence. Thus, health literacy enhancement is essential. This quasi-experimental study examined the effectiveness of a telehealth-integrated health literacy enhancement among people newly diagnosed with hypertension. Fifty participants diagnosed with hypertension within the past year were consecutively recruited from subdistrict health-promoting hospitals in two districts. They were assigned at the cluster level to the experimental or control group (25 per group). The experimental group received usual care plus a six-week telehealth-integrated health literacy enhancement program. The control group received only usual care. Data were collected at baseline and post-intervention using the Personal Health Questionnaire, the Health Literacy Questionnaire, and the Self-Care of Hypertension Inventory. Data were analyzed using descriptive statistics, paired t-tests, and independent t-tests. After the intervention, the experimental group demonstrated significant improvements in health literacy and self-care behaviors, as well as a substantial reduction in systolic blood pressure compared with baseline and the control group. In contrast, no significant differences in diastolic blood pressure were observed. The findings demonstrate the effectiveness of the Health Literacy Enhancement Integrated with Telehealth program in improving health literacy, self-care behaviors, and blood pressure control among people newly diagnosed with hypertension. Nurses can incorporate this program into routine care to improve outcomes, reduce long-term complications, and support continuity of care. However, future studies should include long-term follow-up, a randomized controlled trial, and multisite research before it can be widely used.